Ins Schwarze getroffen? – Zur Prognosegenauigkeit der Steuerschätzungen - Jürgen Wixforth (Wirtschaftsdienst, 2018)
Analysen, die untersuchen wie genau die Steuerschätzungen ausfallen, liegen nur wenige vor. Häufig konzentrieren sie sich auf Steuergesamteinnahmen sowie die Evaluation der Angaben mit kurzem Prognosehorizont. Für die Haushaltsplanung der Länder sind aber auch die Einzelsteuern und weiter in der Zukunft liegende Prognosezieljahre von Bedeutung. – – The article analyses the accuracy of the tax revenue estimates in Germany by comparing the predicted values and the actual tax revenues. Periodic adjustments are also made to take changes in tax law into account. The focus is on both specific types of taxes and on a longer term forecast horizon. The results show that the overall quality of the estimates is good and has improved in recent years. However, there are problems with profit related taxes, which are difficult to predict.
Keywords: H20; H68; H71; 330